2020
DOI: 10.48550/arxiv.2002.07871
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Winding homology of knotoids

Deniz Kutluay

Abstract: Knotoids were introduced by V. Turaev as open-ended knot-type diagrams that generalize knots. Turaev defined a two-variable polynomial invariant of knotoids which encompasses a generalization of the Jones knot polynomial to knotoids. We define a triplygraded homological invariant of knotoids categorifying the Turaev polynomial, called winding homology. Forgetting one of the three gradings gives a generalization of the Khovanov knot homology to knotoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Intrinsic invariants of knotoids, as well as invariants induced from classical and virtual knot invariants have been studied by many researchers. See [3][4][5][14][15][16]19,20,25,26,29,36,39]. Turaev showed that knotoids in S 2 are in one-to-one correspondence with simple Θ-curves and multi-knotoids in S 2 , immersions of the unit interval and a finite number of circles in S 2 , are in one-to-one correspondence with simple theta-links [39].…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic invariants of knotoids, as well as invariants induced from classical and virtual knot invariants have been studied by many researchers. See [3][4][5][14][15][16]19,20,25,26,29,36,39]. Turaev showed that knotoids in S 2 are in one-to-one correspondence with simple Θ-curves and multi-knotoids in S 2 , immersions of the unit interval and a finite number of circles in S 2 , are in one-to-one correspondence with simple theta-links [39].…”
Section: Introductionmentioning
confidence: 99%
“…For example, mentioned above Turaev's extension of the Kauffman bracket polynomial has an additional indeterminate counting intersections of an arc connecting the endpoints with the rest part of a diagram. In [5] The work is supported by the Russian Science Foundation under grant 19-11-00151.…”
Section: Introductionmentioning
confidence: 99%
“…An additional grading in winding homology corresponds with additional indeterminate in the extended bracket polynomial. These improvements makes the polynomial and winding homology more informative than direct analogues of the Kauffman bracket polynomial and Khovanov homology which are also studied in [8] and [5].…”
Section: Introductionmentioning
confidence: 99%
“…The height is the minimum of the number of the intersections over all representative diagrams and all such an arcs disjoint from crossings (see Section 2 for precise definition). Turaev in [13] obtained a lower bound for the height of a knotoid via the extended bracket polynomial which is a purely knotoid generalization of the Kauffman bracket polynomial (see also [11] where corresponding Khovanovtype invariant is constructed). In [5] some known polynomial invariants of virtual knots are extended to the case of classical and virtual knotoids, and, in particular, it is shown that these invariants give a lower bounds for the height of a knotoid.…”
Section: Introductionmentioning
confidence: 99%